Electromagnetic assisted endoscopic submucosal dissection is more efficient than water-jet assisted and conventional ESD in experimental model - Rodríguez Sánchez, Joaquín; Rodríguez Sánchez, Eduardo; de la Santa Belda, Eva; Olivencia, Pilar Palomar; Salmoral Luque, Rosario; Sánchez Alonso, Mónica; Olmedo Camacho, José; Redondo Calvo, Francisco Javier (Endoscopy International Open, 2018)
Background and study aims The adequate visualization of the dissection line, inside the submucosal layer, supposes the main challenging issue in ESD. For this reason, several counter traction methods have been developed focused on overcoming this handicap. One of which, Magnetic anchor guided – ESD (MG-ESD) is an attractive alternative. However, the usefulness of this approach has been scarcely assessed and compared with other ESD strategies. Therefore, the aim of this study is to compare three different ESD alternatives in experimental faction. Methods This was a prospective non-randomized study, in which three different ESD techniques were performed in an ex-vivo gastric porcine model by an endoscopist slight expertise in ESD: conventional ESD, waterjet assisted ESD and MG-ESD. MG-ESD was performed using two different magnets: inner Neodymiun ringed shape magnet attached to the simulated lesions by an endoclip and external electromagnet connected to a Single Output Adjustable 24V/0.3A Power Supply Unit.Results Forty-six ESD procedures were performed: 24 conventional ESD, 12 waterjet-assisted ESD and 10 MG-ESD. Average size of the simulated lesions was 33.86 mm. No differences in terms of safety and efficacy were registered between the three approaches. Nevertheless, MG-ESD proved to be faster and more efficient than conventional ESD and water-jet assisted ESD (min per cm2 10.85 vs. 7.43 vs. 3,41; P = 0.001).Conclusions MG-ESD could be a feasible alternative to conventional ESD even at the beginning of the learning curve. Therefore, researches focused on developing appropriate ESD magnetic devices and further comparative studies must be promoted, in order to assess the reliable usefulness of the magnet-assistance in ESD.